Efficacy of Mindfulness-Based Counseling in Managing Preoperative Anxiety in Women Undergoing Cesarean Section: An Interventional Study - Ansari, Niloufar; Omidvar, Shabnam; Mohsenzadeh Ledari, Farideh; Shirafkan , Hoda; A Azizi, Ali Reza (Shahroud Journal of Medical Sciences, 2025)
Background: Preoperative anxiety, a substantial concern especially for women undergoing cesarean sections, is linked to increased perioperative risks. This research evaluated the effect of mindfulness-based counseling on preoperative anxiety.Methods: This interventional study enrolled 134 pregnant women with prior cesarean delivery from May 10, 2021, to October 20, 2022. They were referred to the perinatology clinic starting in the 35th week of pregnancy. The participants were assigned randomly to two separate groups. The group receiving the intervention underwent five sessions of Mindfulness-focused counseling. Anxiety levels were evaluated using the STAI, while perceived stress was measured with the PSS-14, both before and after the intervention in each group. An independent t-test and ANCOVA were applied to compare the outcomes.Results: After controlling for confounding variables, the mean trait anxiety scores before and after counseling were 40.32±7.63 and 30.51±3.87, respectively, in the intervention group and 38.72±6.26 and 61.64±4.72, respectively, in the control group. The intervention group had a significantly lower mean trait anxiety score compared to the control group. ( [MD: -9.8, F=1879.174, η2= 0.934, P < 0.001). The mean scores for state anxiety before and after counseling were 50.02±7.53 and 30.70±4.28, respectively, in the intervention group and 49.55±6.70 and 62.02±5.36, respectively, in the control group. The intervention group had significantly lower mean state anxiety scores compared to the control group. [MD: -19.32, F=1572.207, η2= 0.923, P < 0.001]. Average scores for perceived stress before and after counseling were 28.78±5.74 and 11.89±3.34, respectively, in the intervention group and 29.06±6.28 and 36.08±4.83, respectively, in the control group. The intervention group had a significantly lower mean state anxiety score compared to the control group [ MD: -16.89, F=1332.892, η2= 0.911, P<0.001].Conclusion: Mindfulness-based counseling decreases stress and anxiety before cesarean section. Nonetheless, additional Randomized Controlled Trials are required prior to reaching a final decision